المراحل التاريخية للأفلام السينمائية في الجزائر - عبدالوهاب، بردق Abdulwahab, Bardaq; بولقدام، نادية Boulqadam, Nadiah (جامعة عبدالحميد بن باديس - كلية العلوم الإجتماعية - مخبر حوار الحضارات والتنوع الثقافي وفلسفة السلم, 2019)
حظيت السينما الجزائرية منذ نشأتها بمكانة مرموقة على المستوى العربي والعالمي، فرغم الأزمات التي مرت بها، إلا أنها استطاعت أن تنتشر عبر وسائل الإعلام الدولية، وأن تأخذ مكانتها في المحافل الدولية، ولعل خير دليل على ذلك، حصولها على السعفة الذهبية في مهرجان كان الدولي عام 1975، للفيلم "وقائع سنين الجمر" للمخرج محمد لخضر حامينة. كما ارتبطت السينما الجزائرية بمحيطها الجغرافي والسياسي والاجتماعي والاقتصادي والثقافي، إلا أنها في الآونة الأخيرة تراجعت وتذبذبت الأعمال السينمائية في الجزائر، وهذا راجع إلى عدة أسباب، كهجرة المخرجين، وعدم وعي الجمهور بدور السينما، وضيق حيز التعبير، ضف إلى ذلك العشرية السوداء (فترة التسعينيات). لابد من اهتمام النقاد والدراسيين والمهتمين بمجال السينما، وان ينهضوا بهذا الفن، والذي يحمل في طياته عدة أهداف منشودة تعمل على رقي وازدهار تفكير المجتمع الجزائري، وهذا من خلال دراستها مواضيع الساعة. فالفيلم السينمائي مثلا يعتبر وثيقة اجتماعية، تسهم في توثيق الأحداث السياسية والاجتماعية والفكرية، ورسم ديناميكية المجتمع، كما يسهم في فهم العلاقة الجدلية بين الإنسان والمجتمع.
Since its inception, Algerian cinema has enjoyed a prominent position on the Arab and international levels. Despite the crises it has experienced, it has been able to spread through the international media and to take its place in international forums. In 1975, for the film "The Chronicles of the Years" by Mohamed Lakhdar Hamina. Algerian cinema has also been associated with its geographical, political, social, economic and cultural surroundings. Recently, however, the film business in Algeria has declined. This is due to several reasons, such as emigration of filmmakers, the public's lack of awareness of cinemas and the narrow space of expression, (The 1990s). It is necessary to pay attention to critics, academics and those interested in the field of cinema, and to promote this art, which carries with it a number of goals that seek to promote and flourish the thinking of Algerian society, and this through the study of current topics. The film, for example, is a social document that contributes to documenting political, social and intellectual events, drawing the dynamics of society and contributing to understanding the dialectical relationship between man and society.
Keywords: الافلام -- السينما -- الوثيقة الاجتماعية